2018
DOI: 10.1101/432039
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classifying cold stress responses of inbred maize seedlings using RGB imaging

Abstract: 16Increasing the tolerance of maize seedlings to low temperature episodes could mitigate the 17 effects of increasing climate variability on yield. To aid progress toward this goal, we established 18 a growth chamber-based system for subjecting seedlings of 40 maize inbred genotypes to a 19 defined, temporary cold stress while collecting digital profile images over a 9-day time course. 20Image analysis performed with PlantCV software quantified shoot height, shoot area, 14 other 21 morphological traits, and ne… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…The first experiment (E1) consisted of three replicates of five genotypes of maize seedlings under four treatment groups (control, cold, salt, and heat) imaged at a single time point. The chosen genotypes were previously demonstrated to differ in morphological responses to cold stress (Enders et al., 2019). The second experiment (E2) consists of two genotypes under four treatment groups (control and three severities of salt stress) imaged at three timepoints (immediately before the stress, 2 d following the stress treatment, and 4 d after following the stress treatment).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first experiment (E1) consisted of three replicates of five genotypes of maize seedlings under four treatment groups (control, cold, salt, and heat) imaged at a single time point. The chosen genotypes were previously demonstrated to differ in morphological responses to cold stress (Enders et al., 2019). The second experiment (E2) consists of two genotypes under four treatment groups (control and three severities of salt stress) imaged at three timepoints (immediately before the stress, 2 d following the stress treatment, and 4 d after following the stress treatment).…”
Section: Resultsmentioning
confidence: 99%
“…Red–green–blue side‐view images of each set of plants were collected immediately following hyperspectral data collection using the procedures specified in Enders et al. (2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown the applicability of RGB to obtain relevant information about plants status, e.g. to evaluate growth and flowering dynamics (Ge, Bai, Stoerger, Schnable, 2016;Guo, Fukatsu, Ninomiya, 2015), growth of plant shoots (Golzarian et al, 2011), and yield traits (Fernandez-Gallego et al, 2019), to count seedlings in a field (Liuet al, 2016), predict plant density (Ranđelović et al, 2020), plant stress (Enders et al, 2019;Briglia et al, 2019;Li et al, 2018) and more. Description of the typical devices and software used in plant phenotyping measurement are listed in Table 1.…”
Section: Visible Spectral Range Imaging (Rgb)mentioning
confidence: 99%
“…Low temperature is a key environmental factor limiting the geographical distribution and productivity of crops that are adapted to tropical/subtropical climates (DeRidder & Crafts-Brandner, 2008;Yadav, 2010). Depending on the onset and duration of cold stress, the severity of its impact to plant growth and development varies (Enders et al, 2019). Some of the earliest responses of a plant to cold exposure include modifications in cell membrane flexibility, changes in ionic fluxes, and reduced cytoplasmic streaming, accompanied by the excessive generation of highly reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%